2006
DOI: 10.1590/s0100-204x2006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética em café conilon

Abstract: Resumo -O objetivo deste trabalho foi avaliar a divergência genética entre 32 clones de café conilon (Coffea canephora Pierre ex Frohener) componentes de três variedades clonais melhoradas, com vistas à identificação dos mais dissimilares, para o estabelecimento de programas de cruzamentos dirigidos. A divergência genética foi avaliada por procedimentos multivariados: distância generalizada de Mahalanobis, método de agrupamento de otimização de Tocher e técnica de variáveis canônicas. Sete caracteres foram ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 6 publications
2
36
1
9
Order By: Relevance
“…Other genetic studies involving C. canephora also highlighted the existence of differences between genotypes regard different characteristics, such as crop yield, number of orthotropic and plagiotropic branches emitted per plant, canopy size, plant height, fruit size, beverage quality, maturation cycle, percentage of fruits with empty locules, length of reproductive branches, and stem diameter (FONSECA, 1999;FERREIRA, 2003;FONSECA et al, 2006;FERRÃO et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other genetic studies involving C. canephora also highlighted the existence of differences between genotypes regard different characteristics, such as crop yield, number of orthotropic and plagiotropic branches emitted per plant, canopy size, plant height, fruit size, beverage quality, maturation cycle, percentage of fruits with empty locules, length of reproductive branches, and stem diameter (FONSECA, 1999;FERREIRA, 2003;FONSECA et al, 2006;FERRÃO et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Coffea canephora presents high crossfertilisation and self-incompatibility; therefore, populations of this species of coffee tend to express significant variability with regard to many agronomic traits, such as plant architecture, duration of ripening cycle, uniformity of maturation, size and weight of grains, susceptibility to coffee pests, and productive potential (FONSECA, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the most appropriate method should be performed according to the desired precision, the ease of analysis and the way the data were obtained (Fonseca et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The number of groups demonstrates the broad variability among the genotypes tested. Fonseca et al (2006), working with 32 genotypes of Conilon coffee, and Ivoglo et al (2008), with 21 offspring that were genetically half Conilon coffee, observed the formation of three and four groups, respectively. Dias et al (2005) evaluated 25 progenies of Arabica coffee, observed the formation of five distinct groups.…”
Section: Genetic Divergencementioning
confidence: 99%